If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 100 + -1x Solving 2x = 100 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 2x + x = 100 + -1x + x Combine like terms: 2x + x = 3x 3x = 100 + -1x + x Combine like terms: -1x + x = 0 3x = 100 + 0 3x = 100 Divide each side by '3'. x = 33.33333333 Simplifying x = 33.33333333
| (-5/7)a=15 | | F(x+9)=x^2-8x+8 | | 3(2y+3)-4(y+1)=7y-10 | | 2+12=13 | | 16=4+15 | | f(x)=-2x+12 | | 2x-9-9x-8= | | 2p+7p-3p+1p+6p= | | 2(2t+44)=.75(24-8t) | | 3/10-7/15 | | Y=10+0.8Y+10 | | y=10+0.9Y+10 | | F(5)=x+1 | | 2(4z+1)-4(5z-4)-13z= | | 4x-14-3x=-8-12 | | http://k/6=4/3 | | 3/4j=6 | | 5x-10+65=180 | | -6(7k-5)=-17 | | 5(3+6z)=18 | | 7-2(1-5n)=26 | | 0.02x=0.04 | | 122=2(12x-9) | | (y)/(y-5)=x | | (3x+4)(x-9)=0 | | 10y-3=5y-18 | | 30=-7+4(s-5) | | (m/(m-5))=x | | 4(a-1)=-1+a | | 24=(n-5) | | -23+6c=2(7c-8) | | 3a-2+9a=-18 |